Informação móvel para todos : acessibilidade em aplicativos jornalísticos para dispositivos móveis - Goss, Bruna Marcon (2015)
This work observes the use of news apps by vision-impaired people, what are the possibilities of news content appropriation by this public in this platform. Starting with Human Computer Interaction, interfaces and usability studies, central concepts are defined in order to situate what is the relationship between people and technological devices and how the way to interact with them has evolved with time, as well as how these concepts tend to not consider an important part of the population: disabled people. By going through concepts of handicaps, accessibility and assistive technologies, it is possible to perceive the space this part of population has in society and how technological devices can contribute to social inclusion. These former concepts are important to understand the concept of mobility and post-PC devices (Baxter-Reynolds, 2013), that change how information is used and consumed, as well as the ideas of interfaces and modes of interaction.The space journalism takes in this moment is evaluated: the struggles that come with the desktop-web model and the possibilities of new journalism products for mobile devices. Three news apps are evaluated: Globo.com, Veja and Circa by three visually impaired people, using smartphones with the two most popular mobile operational systems – iOS and Android. The results demonstrate that there is already a good improvement in accessibility, mostly on the devices and operational systems, but the is still a long way to go when it comes to information organization and identification of elements such as images and buttons in order to provide visually impaired people a good and usable experience when consuming news on their devices.